RANCANGAN DESIGN TAMBANG TERBUKA JANGKA MENENGAH PADA TAMBANG BATUBARA DI WILAYAH TOWNSITE PT.BUKIT ASAM (PERSERO) TBK, TANJUNG ENIM, SUMATERA SELATAN - Diah Wulandari; Dedi Yulhendra; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2015)
PT Bukit Asam (Persero), Tbk is one of STATE-OWNED company engaged in the coal. Referring to Government Regulation No. 70 of 2009 about energy conservation management has to be planned with and integrated in order to preserve domestic energy resources as well as increasing efficiency in its use. In order to support the energy conservation policy, PT Bukit Asam (Persero) Tbk do optimization of final mining Pit. In an attempt to optimization of Mine Air Laya mine area expansion required water laya to optimize an existing backup.Therefore, PT Bukit Asam (Persero), Tbk is planning an expansion of the mine in the Townsite and plan long-term long-term planning will be made next his secondary.This research was conducted to find out the design of the mine, the mining sequence, scheduling production, mining costs and tool needs. Final does is analyze the quarerly planning of open mines and mine feasibility in terms of economical.Topographic data, the contour of the spreading of coal and mine design that had been planned for 5 years with a target of mining production 4.000.000 ton/year. Transport equipment and tools fit in the first year until the fifth year of the appropriate stable using 4 eksavator Pc 400 and nine truck Scania P30 with a capacity of 30 tons. While, mine made access roads with a width of 15 meters based on the widest transport tool. There is a disposal area that can accommodate 124.918.226 bcm of overburden and interburden. Based on the use of mining equipment, equipment investment of 26.870.826 and net income of the proceeds of 187.616.010. It can be concluded that the medium-term in the area of mining Townsite deserves to be mined and meet production targets set.